Estudo retrospectivo dos procedimentos anestésicos realizados em cães e gatos submetidos a neurocirurgias - Godoi, Daniella Aparecida; Antunes, Mariana Isa Poci Palumbo [UNESP]; Arias, Mônica Vicky Bahr; Grumadas, Carmen Esther; Reia, Angelita Zanata; Nagashima, Julio Ken (Universidade Estadual de Londrina, 2009)
Neurosurgeries are frequent in the routine of veterinary hospitals and, therefore, knowledge of the different anesthetic protocols to be used for each patient is necessary to prevent the morbity and mortality in the after and trans-surgical period. The objectives of this study were to evaluate the anesthetic protocols used in patients undergoing neurosurgeries; the results of those protocols; the rate of complications, and if those complications are related to the duration of the anesthesia time. We studied the anesthetical data of 52 dogs and two cats submitted to neurosurgery between January of 2003 and December of 2006, in the Veterinary Hospital of UEL. Findings showed that the main protocols used were propofol for induction and halothane or isofluorane for maintenance of the anesthesia. These protocols induced adequate anesthesia for the surgical procedure and did not occur complications during the anesthetic period in 37/54 (68,5%) of the cases. 7/19 (36.8%) of the complications observed occurred in patients submitted to anesthesia with halothane and 8/32 (25.2%) in patients with isofluorane. The complication most observed in this study was bradicardy, which occurred in 15/54 (27.8%) of the patients. Two deaths occurred in patients submitted to slot cervical. Good knowledge of the neurological disease and of surgical and anesthetic techniques are essential to prevent alterations in the central nervous system caused by the drugs, disease or association of these factors.
Retrospective study of anesthetic proceedings realized in dogs and cats undergoing neurosurgeries
Keywords: Anesthesia; Cats; Complications; Dogs; Neurosurgery